2007
DOI: 10.1016/j.ijid.2006.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Toxin A-negative, toxin B-positive Clostridium difficile

Abstract: Clostridium difficile is a major cause of infectious diarrhea in hospitalized patients. Many pathogenic strains of Clostridium difficile produce two toxins TcdA and TcdB, both of which are pro-inflammatory and enterotoxic in human intestine. Clinically relevant toxin A-negative, toxin B-positive (A(-)B(+)) strains of Clostridium difficile that cause diarrhea and colitis in humans have been isolated with increasing frequency worldwide. This perspective describes these important toxin variant strains and highlig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
128
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(139 citation statements)
references
References 53 publications
6
128
0
3
Order By: Relevance
“…Toxin B does not cause fluid accumulation but is extremely cytopathic for tissuecultured cells [130]. These toxins are encoded by two genes, tcdA and tcdB, mapping to a 19.6 kb pathogenicity locus (PaLoc) and containing 3 additional regulatory genes, tcdC, tcdR, and tcdE, that are responsible for the synthesis and regulation of toxins A and B [135]. Deletions, insertions, or polymorphic restriction sites in one or more of the PaLoc genes can result in toxin variant strains that produce either toxin A or toxin B [135].…”
Section: Difficile Characteristics and Its Toxinsmentioning
confidence: 99%
“…Toxin B does not cause fluid accumulation but is extremely cytopathic for tissuecultured cells [130]. These toxins are encoded by two genes, tcdA and tcdB, mapping to a 19.6 kb pathogenicity locus (PaLoc) and containing 3 additional regulatory genes, tcdC, tcdR, and tcdE, that are responsible for the synthesis and regulation of toxins A and B [135]. Deletions, insertions, or polymorphic restriction sites in one or more of the PaLoc genes can result in toxin variant strains that produce either toxin A or toxin B [135].…”
Section: Difficile Characteristics and Its Toxinsmentioning
confidence: 99%
“…12 It was initially reported that anti-TcdA antibodies were sufficient to protect the host against CDI. 13,14 However, recent studies demonstrated an even more important role of TcdB in the pathogenesis of CDI, [15][16][17][18] suggesting that an effective vaccine should target both toxins.…”
Section: Introductionmentioning
confidence: 99%
“…25 There are fewer reports on vaccine development based on toxin B and there is even less information on whether other regions of C. difficile toxins can also serve as protective antigens. With recent findings that toxin B is essential for virulence of C. difficile 6 and the fact that naturally occurring A-B+ strains exist and may cause clinical C. difficile infection, 26,27 it is now important to identify novel region(s) on toxin B antigens that can maximize the protective efficacy of C. difficile vaccines. In the current study, we used the DNA vaccination approach as a tool to screen the immunogenicity of various toxin A and toxin B fragments.…”
Section: Introductionmentioning
confidence: 99%